2015
DOI: 10.1057/ces.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Policy in Argentina During 2002–2013

Abstract: We analyze Argentina's macroeconomic policy and performance between 2003 and 2013. The period began with a rapid recovery following the 2001-02 crisis. Recovery then turned into strong and sustained growth. By late 2011, despite a very favorable external context, Argentina entered a stagflationary trap. Facing a visible lack of foreign exchange, the authorities introduced and reinforced a series of controls, which did not prevent a currency crisis in late 2013 and early 2014. We argue that macroeconomic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
(9 reference statements)
0
15
0
7
Order By: Relevance
“…There are a variety of historical experiences that support the claim that stable and competitive real exchange rate (SCRER) policies are good for economic development, as demonstrated by a number of Asian economies (Rodrik, 2008;Razmi et al, 2012), and more recently by Argentina during 2003-2008(Damill, Frenkel, and Rapetti, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of historical experiences that support the claim that stable and competitive real exchange rate (SCRER) policies are good for economic development, as demonstrated by a number of Asian economies (Rodrik, 2008;Razmi et al, 2012), and more recently by Argentina during 2003-2008(Damill, Frenkel, and Rapetti, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The recent case of Argentina is an indication of these risks: When the country followed a SCRER policy (2003)(2004)(2005)(2006)(2007)(2008), the macroeconomic performance was successful. When that strategy stopped being followed (since 2010), economic performance was mediocre (Damill, Frenkel, and Rapetti, 2015).…”
Section: Additional Policy Coordination Challenges With the Implementmentioning
confidence: 99%
“…Certainly because this is too a recent period to study 1 . In fact, there are only two closely related works: the one of Damill et al (2015), who analyze the period 2002-2013 and state that stagflation observed in Argentina since 2011 was due to "a shortsighted strategy that sought to stimulate aggregate demand disregarding the impacts on inflation, the balance of payments and the fiscal deficit". And the one by Gerchunoff and Rapetti (2016), who do a historical analysis of Argentina for the period 1930-2015 and find that, since 2008, "economic policy was based on fiscal and monetary expansion to satisfy social aspirations".…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the expansion of State intervention has been considered one of the main characteristics of "populist" governments (Ferreres 2011, Damill et al 2015, criticized by confusing policies which are unsustainable in tandem with the economic well-being, and by wasting the wealth of the prosperous years on policies that leave no favorable results in the long term (Cachanosky 2017).…”
Section: Introductionmentioning
confidence: 99%